MICROBIOLOGICAL SCREENING FOR VAGINAL HEALTH: DETECTING Candida albicans AND Staphylococcus aureus IN FEMALE STUDENT’S URINE - Nasywaa Amalia; Maya Sari Sari; Arief Fadillah; RA. Dewi Maria Yuliani (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Vaginal discharge (leucorrhea) is a common condition in women and may be physiological or pathological. Pathological leucorrhea often results from infections caused by microorganisms such as fungi and bacteria, associated with poor genital hygiene. This study aimed to isolate and identify the microorganisms causing leucorrhea symptoms in the urine of female students at Poltekkes Kemenkes Banten, emphasizing its relevance to preventive health efforts through cross-professional collaboration in microbiology and reproductive health. Twenty urine samples from second-year students showing premenstrual leucorrhea symptoms were collected using purposive sampling. Laboratory analyses included fungal culture on Sabouraud Dextrose Agar (SDA), germ tube testing for Candida albicans, bacterial culture on Nutrient Agar (NA), catalase testing, and Gram staining. The results showed that 7 samples (35%) were positive for Candida albicans and 2 samples (10%) were positive for Staphylococcus aureus. Both organisms are recognized as causative agents of pathological leucorrhea and reproductive tract infections. The findings highlight the importance of maintaining genital hygiene and the integration of microbiological screening into health education to prevent infections related to women’s reproductive health. This study underscores the role of interprofessional collaboration in laboratory science and health education for early detection and management of infection-related conditions, contributing to the prevention of non-communicable complications through integrated health services.